REMAP-RT in the Circulatory System Material to Improve Students Cognitive Learning Output - Nuryani Nuryani; Much Fuad Saifuddin; Azkia Hasna Nuha Imana; Devi Istiqomah; Mia Setia Haningsih; Via Puspa Ardani; Anita Yuni Astuti; Destri Ratna Ma'rifah (Mangifera Edu, 2020)
Learning outcomes are still a benchmark of learning success, with good learning outcomes signifying mastery of knowledge that can be implemented in life. Students require to be accustomed to reading before beginning learning, to be able to manage information from learning resources.. This study aims to study the Remap-RT learning model to improve student learning outcomes by looking at the results of pretest and posttest students of class VIII E Muhammadiyah 2 Kalasan. The method used in this research is CAR (Classroom Action Research). The subject in this study was a student at VIII E of SMP Muhammadiyah 2. Data obtained by using the test twice in both cycle, cycle I and cycle II. Based on the results of the pretest and posttest the average value of class VIII E in the last cycle is higher than the first cycle. Based on these findings it can be concluded that there is an improvement in the learning process and differences in student learning outcomes using the Remap-RT learning model.